HIPNOBREASTFEEDING DAN PIJAT OKSITOSIN BERPENGARUH TERHADAP PENGELUARAN KOLOSTRUM PADA IBU POST PARTUM - Hamidah Hamidah; Shentya Fitriana (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
Woman are blessed by The Almight God to conceive, give birth, and breastfeed. The nature given to the woman is characterized by the existence of its reproductive organs, such as uterus where the fetus grows and develops in the womb, breasts which breastfeed milk is produced so that the mother can breastfeed her baby at the beginning of childbirth. It means that all women have the potential to breastfeed their babies, just as their potential to conceive and deliver (Perinesia, 2010). At the early labor many post-partum mothers complain that their breastfeed milk cannot or not yet to be released that they cannot give colostrums to their baby at the beginning of their birth. One effort that can be done to help release the colostrum is by doing hypnobreasfeeding, oxytocin massage to the post-partum mothers 2-6 hours.This study discusses the effect of hypnobreastfeeding, the oxytocin massage on the releasing time of colostrum to the post-partum mothers 2-6 hours. This research used quantitative method. Respondents are post-partum mothers who performed hypnobreasfeeding, massage of oxytocin. The research design was Quasi Experiment. Sampling was done by purposive sampling of 70 respondents. The research results showed that parity was related to colostrum release at 4 hours post partum (p value = 0.020). Multivariate analysis proved that the most dominant factor that influenced colostrum release was multi-gravid parity by hypnobreastfeeding and oxytocin massage at 4 hours of post partum.